Analisis Faktor Dan Cara Penanganan Bullying - Sofhie Awalia Ajoen Vania (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
This study aims to analyze the factors influencing bullying behavior in children, as well as the ways of addressing bullying behavior within the family environment by parents and within the school environment by the school authorities. The research subjects are children aged 9 to 12 years, parents, and teachers, from whom data is collected to understand the causes and solutions to bullying behavior. A qualitative research approach is employed, involving observation, interviews, and documentation of the research subjects. The study is conducted at the Mutiara Titipan Illahi Foundation in Tasikmalaya. The research findings indicate that the factors leading to bullying activities include the perpetrators feeling stronger and more powerful in front of their peers, as well as family factors such as lack of harmony and deep communication within the family. The efforts made by teachers involve providing intensive guidance and moral support to both the bullies and the victims, thus effectively addressing bullying activities. Parents' efforts in dealing with bullying perpetrators involve increasing the level of communication between parents and children, so that children feel supervised and experience a deterrent effect.